THE IMPACT OF MUTANTION IN THE ACTIVE SITE TO LIPASE AND GELATINASE ACTIVITIES OF LIPASE A FROM BACILLUS SUBTILIS FS2 - Thanh, Nguyễn Hồng; Nguyệt, Phùng Thu; Hult, Karl; Hải, Trương Nam (Vietnam Journal of Biotechnology, 2013)
Recombinant lipase A (rLipA) from Bacillus subtilis FS2 was determined to have both lipase and gelatinase activities, in which gelatinase is promiscuous activity of this enzyme. Mutants S77C, D133N and H156N in the active site of lipase were created using mega-primer method. Three mutants were cloned and successfully expressed in the cells E. coli BL21 (DE3). However, only two mutants S77C and H156N were successfully purified for activity assays whereas mutant D133N existed in insoluble form. Kinetic parameters Km and Vmax for lipase and gelatinase activity of recombiant protein (rLipA) were calculated and compared to that of mutants. Mutants S77C and H156N showed remarkably decreased lipase activity however S77C increased gelatinase activity in 20 folds. Possible explaination might be that mutants at the active site of rLipA altered dimension structure and hydrogen bonding network of enzyme result in the changing of enzyme-substrate binding, thereby lipase would bind to gelatin and facilitate for cleavage reaction. The amino acids potential for gelatinase activity might be located in other sites in the active site of this enzyme.